2017
DOI: 10.1002/ange.201703369
|View full text |Cite
|
Sign up to set email alerts
|

A Modular Flow Design for the meta‐Selective C−H Arylation of Anilines

Abstract: Described herein is an effective and practical modular flow design for the meta-selective CÀHa rylation of anilines.T he design consists of four continuous-flowm odules (i.e., diaryliodonium salt synthesis,m eta-selective CÀHa rylation, inline copper extraction, and aniline deprotection) which can be operated either individually or consecutively to provide direct access to meta-arylated anilines.W ith at otal residence time of 1hour,t he desired product could be obtained in high yield and excellent purity with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 76 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…Based on limited safety information on hypervalent iodine in the literature 11 and the potential for exothermic events that have been suggested in a related diaryliodonium salt synthesis, 12 we conducted a safety evaluation during the development of this procedure. We specifically focused on the potential thermal hazards of I-oxidation with m-CPBA and the thermal stability of the hypervalent iodine species (intermediate 1 and product 2).…”
Section: Discussionmentioning
confidence: 99%
“…Based on limited safety information on hypervalent iodine in the literature 11 and the potential for exothermic events that have been suggested in a related diaryliodonium salt synthesis, 12 we conducted a safety evaluation during the development of this procedure. We specifically focused on the potential thermal hazards of I-oxidation with m-CPBA and the thermal stability of the hypervalent iodine species (intermediate 1 and product 2).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, isotopic labeling and 1 H‐NMR results confirmed that the H* species used for 4‐NBA ERR were derived from water (Figure 9I). 135,136 The OH* radical generated in the first step of water dissociation was identified as the active species of HMFOR by electron spin resonance (Figure 9J). 137 The enhanced electronic conductivity and electron transfer in heterojunctions, as well as the well‐defined reaction pathways and their pairing advantages, provide guidance for the sustainable synthesis of various value‐added chemicals via paired electrocatalysis.…”
Section: Coupling Reactionsmentioning
confidence: 99%
“…With mono-substituted arenes, a high degree of regioselectivity was observed irrespective of their electronic nature (Scheme 1b). While toluene (14), anisole (15), and chlorobenzene (16) provided high para-selectivity, nitrobenzene (18), trifluoromethylbenzene (19), and benzaldehyde (20) gave high metaselectivity, and with fluorobenzene (21) ortho-selectivity was observed. The intriguing aspects continued with paraolefination of free phenol (17) obviating the prior protection protocol.…”
Section: Resultsmentioning
confidence: 99%